A Different Take: Reflections on an intergenerational participatory research project on child poverty - Chester Howarth; Camilla McCartney; Maria Mansfield; Gill Main (Social Work and Society, 2021)
This article provides reflections on 'a Different Take', a participatory action research (PAR) project which aimed to amplify the knowledge of children, young people and parents in anti-poverty research, policy and practice. In recent decades there has been an increasing emphasis on experiential knowledge in understanding poverty, especially through the use of PAR; this has emerged in parallel with sociological studies of childhood which emphasise the importance of considering children as active agents whose perspectives should be included in research. While these two developments are ostensibly strongly interrelated, children's perspectives remain largely absent in research and in agenda-setting around child poverty. In this article we offer some critical reflections on an effort to bring the two together through a recent inter-generational PAR project to evidence the ways in which this approach: (1) generated new child- and family-specific knowledge; (2) added conceptually to poverty research methodology with implications for future research; and (3) illustrated the potential for local authority policy-makers to embed the knowledge of children and adults living in poverty into their policies and practices. These reflections may be useful for practitioners and policymakers working with disadvantaged children, young people and families, and may provide ideas for how intergenerational PAR can serve to holistically embed the knowledge of those impacted by poverty in research, practice and policy.